2019
DOI: 10.1016/j.jweia.2019.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative assessment of the bi-stable states in the wake of a finite-width double backward facing step

Abstract: A B S T R A C TThe flow past a simplified frigate shape model which is analogous to a finite-width double backward facing step is investigated numerically using well-resolved large eddy simulations at Re ' 8 Â 10 4 . The geometric configuration of this model permits the occurrence of bi-stable flow states, with an asymmetrical flow topology being observed in the lateral midplane behind each step. In each flow state, the flow at the top step is anti-symmetrical to that observed on the bottom step, and the two f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Herry et al (2011) observed a bi-stability downstream of the first step. This was investigated further in the studies of Rao et al (2019) and Zhang et al (2021), who employed geometries more representative of ships upstream of the first step. However, the authors are not aware of any studies that have systematically varied the streamwise separation between the two steps to study the interaction of the separated flow regions.…”
Section: Introductionmentioning
confidence: 99%
“…Herry et al (2011) observed a bi-stability downstream of the first step. This was investigated further in the studies of Rao et al (2019) and Zhang et al (2021), who employed geometries more representative of ships upstream of the first step. However, the authors are not aware of any studies that have systematically varied the streamwise separation between the two steps to study the interaction of the separated flow regions.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last several years, many studies have focused on using nanofluids with separation flow in BFSs and FFSs, which have been considered by various researchers [18][19][20][21][22][23][24][25][26][27][28][29][30] with similar conclusions. Recently, the modeling of turbulent heat transfer over a microscale BFS was presented by Sadeq et al [31].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that Case 4 has less control effectiveness with lower pressure recovery, and its drag reduction will require higher energy consumption. Note that the drag reduction of 5.34% and 6.22% may sound small, but is much more significant compared to the drag reduction of less than 2% achieved by the base cavity flow control applied on the SFS2 ship model in Rao et al (2019). Fig.…”
Section: Flow Control Resultsmentioning
confidence: 90%
“…For the present case, 𝛥𝑠 + is less than 55 and the maximum 𝛥𝑙 + is 21. Based on various numerical studies on the ship model with the grid size ranging from 6 to 21 million cells (Zhang et al, 2018;Rao et al, 2019;Zhang et al, 2021), the grid resolution of more than 37 million cells for the present study is sufficient. Therefore, no further grid independent study is conducted.…”
Section: Numerical Setupmentioning
confidence: 99%